Linksnių sinkretizmo ir analogijos vaidmuo kai kurių linksnių formų raidoje - Rosinas, Albertas (Baltistica, 2000)
THE ROLE OF CASE SYNCRETISM AND ANALOGY IN THE EVOLUTION OF SOME CASE FORMSThe article presents an analysis of the role of case syncretism and analogy in the evolution of some case forms. The data drawn from the old manuscripts and dialects attest to the following: 1. In Žemaitian subdialects, the oxytonic i-stem nominal nominative singular form (aus)-iẽ evolved under the influ¬ence of oxytonic ē-stem nominal nominative and inessive singular syncretic forms according to the pro¬portional analogy formula: ines. sing. (žuol)-iẽ : nom. sing. (žuol)-iẽ = ines. sing, (aus)-iẽ : nom. sing, x, where x = (aus)-iẽ. 2. Both the Žemaitian i-stem resp. (i)io-stem and C-stem inessive singular ending -ie and the Aukštaitian ending –ėj(e) as well as the Latvian -ē, (-e) were introduced from the ē-stem inessive singular as a result of the merger of ē-stem and i-stem nouns brought about by word-final phonological changes. 3. The said ending first occurred in the barytonic i-stem nominal paradigm, and later it was introduced into both the masculine and the feminine oxytonic nominal paradigm. 4. As the old (i)io-stem accusative singular form was replaced by the i-stem form in the whole Baltic area, in Žemaitian (and their nearer neighbours’) subdialects, the inessive ending, as a superstable and maximally iconic inflection, was introduced into the (i)io-stem paradigm, too, on the model of the i-stem (and C-stem) accusative and inessive singular. 5. In most Žemaitian subdialects, the old i-stem inessive plural form in -isu was modified to -ies(e) on the ē-stem model. 6. The o-stem inessive singular form (lauk)-é evolved from the syntactic construction *laukei + en -> *laukē + en -> *laukén by eliminating the first compo¬nent -ē under the regulating influence of the structural model of (i)o-stem adjectival and pronominal dative and inessive singular forms. 7. In the Latvian language, the (i)o-stem locative singular form ending -ā was introduced from the (i)ā-stem not because of the phonetically determined syncretism of the old ending of the locative *(darb)-i (
Keywords: istorinė kalbotyra; vardažodis; linksnis